OFDM-based overlay systems a promising approach for enhancing spectral efficiency. - Berthold, Ulrich (IEEE Communications magazine)
Recently, several approaches for increasing spectral efficiency have been proposed to overcome the scarcity of spectral resources and to ensure that the ever-growing demand for high-data rate mobile communications can be met in the future. In this article, we focus on OFDM-based overlay systems that share a frequency band with already existing systems without degrading their performance. This is achieved by temporarily using those parts of the common frequency band that are currently not used by the licensed system. In particular, we focus on design issues for the physical layer as well as the medium access control layer and propose appropriate solutions for enabling coexistence. As a result, our investigations show that OFDM-based overlay systems are a promising approach for enhancing spectral efficiency.